PERANCANGAN MEDIA PROMOSI KOMUNITAS SENI KUFLET PADANG PANJANG - Akbar, Rizka Lovani; Sudiani, Yoni; Rahman, Fadlul (VCoDe : Visual Communication Design Journal, 2025)
The Kuflet Art Community is an art community focused on literature and theater, offering a platform for artists to express their creativity as part of a group with shared interests. An effective promotional media concept is necessary to address the challenges in reaching a wider audience and strengthening the community's image, which is highly dedicated to literacy. The target audience for this design includes artists, art practitioners, and anyone involved in the arts in Padang Panjang City. The methods used in designing the promotional media include data collection through observation, interviews, and questionnaires to understand the needs and characteristics of the community. The design process is carried out by applying design and animation principles relevant to the identity of the Kuflet Art Community. The promotional media is designed to provide information about the community's programs, achievements, and relationships in an engaging and communicative manner. The design results include promotional media capable of convincing and inviting the target audience to join the Kuflet Art Community and increasing public awareness of the community's existence. The media mix produced includes videos, posters, flyers, brochures, x-banners, stamps, business cards, lanyards, and various merchandise. This design is expected to be the first step in a broader sustainable promotional strategy.